Menggali Persepsi Dan Pengalaman Stigma Sosial Mahasiswa Penerima Kartu Indonesia Pintar Kuliah (Kipk) Dalam Konteks Gaya Hidup Konsumerisme - Tommy Harzeina; Dewien Nabielah Agustin (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2025)
The Indonesia Smart Card Program for College (KIP Kuliah) is a form of government intervention to expand access to higher education for students from low-income families. Although this program provides significant financial benefits, KIP Kuliah recipients often face social stigma from their surroundings. This study aims to uncover the experiences and perceptions of KIP Kuliah recipient students regarding the social stigma they experience, especially in the context of lifestyle and consumerism. This study uses a qualitative approach with an in-depth interview method with three informants who are KIP Kuliah recipient students. The results of the study indicate that the stigma experienced by students includes negative labeling and stereotypes that associate the status of recipients with consumer behavior that is considered inappropriate, such as hanging out, traveling, and using expensive electronic goods. The public tends to judge only from the outside appearance without considering the context, such as academic needs, family support, or the results of students' personal efforts. From the perspective of Erving Goffman's stigma theory, this finding illustrates the tension between virtual social identity (public expectations) and actual social identity (student reality). In response to stigma, students demonstrate impression management efforts through academic achievement, organizational involvement, and adjusted lifestyles. This study concludes that although KIP Kuliah has succeeded in increasing access to education, recipients still face social challenges that require attention. An educational approach is needed to dismantle the stigma and build a more empathetic understanding of the social realities of students receiving educational assistance.